Analysis Of Quality Of Science Learning On Material Properties Of Light In Sds Bina Satria Mulia - Hendra, Elvina Syavhira; Nasution, Fadillah Ramadhani (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The purpose of this research is to improve the quality of science learning in class IV through. This study used a Classroom Action Research design which was carried out in three cycles with one meeting each cycle, which consisted of planning, implementing, observing, and reflecting. Data collection techniques in this study were observation, interviews, tests, documentation and field notes. Data analysis techniques using quantitative and qualitative analysis. The results in this study were that the score of the teacher's skills in cycle I was 51 (good), 57 in cycle II (good), and 68 in cycle III (very good). The total score of student activity in cycle I was 17 (good), 23 in cycle II (good), and 27 in cycle III (very good). The percentage of completeness of student learning outcomes is 73.81% in cycle I, 83.33% in cycle II, and 100% in cycle III. The conclusion in this study is that through the Example Non-Example model assisted by audio-visual media can improve the quality of science learning.Keywords: Science Learning Quality, Material Properties of Light